(untitled) (Research, Society and Development, 2022)
Information and Communication Technologies (CITs) in the current scenario is even more, touching on how people understand and resignify the world, society and cultures. It appears that the incorporation of these digital technologies has been gaining prominence in educational practices and so that the school, as a social institution, must have the discernment of implementation needs for the use of ICTs in their daily practices. Thus, this article aimed to reflect on these educational practices as a focus on ICTs. The research methodology was based on bibliographic sources in a qualitative approach. Obtaining as results, the importance of Digital Inclusion in Education and in the continuing education process of teachers, being the difference in the learning method used, in addition to fostering Innovation in Education, redefining educational practices and challenging possible difficulties inherent in the use and inclusion of ICTs in this Information Age.